Prevalence of diabetes and prediabetes in district Swat Pakistan - Akhtar, Sohail; Ali Shah, Syed Wadood; Javed, Saleem; Alina, Ayisham (Journal of the Pakistan Medical Association, 2021)
Abstract Objective: To determine the prevalence of pre-diabetes and diabetes and its associated risk factors in adult population. Methods: The cross-sectional population-based study was conducted from January to March 2018 in urban and rural areas of Swat, Pakistan, and comprised subjects aged 20-89 years. After a minimum 10-hour overnight fast, blood glucose was tested for pre-diabetes and diabetes according to the World Health Organization recommendations. Data was analysed using SPSS 21. Results: Of the 1447 subjects, 837 (58%) were females and 610 (42%) males. The largest age group was 20-29 years with 322 (22.3) subjects. Pre-diabetes was found in 309 (21.4%) subjects and diabetes in 138 (9.52%). Higher age, urbanisation, family history of diabetes, weight, exercise, hypertension, monthly income and education were found to be significant risk factors for pre-diabetes and diabetes (p<0.05). Conclusion: Every 10th resident of Swat was found to have diabetes, and every one in five had pre-diabetes. Key Words: Prevalence, Diabetes, Pre-diabetes, District Swat, Pakistan. Continuous...